2002
DOI: 10.1076/ejom.40.4.219.16696
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP-Receptor Proteins in Human Salivary Glands

Abstract: In mammalian species, cyclic AMP receptor proteins (cARP) are the regulatory (R) subunits of cyclic AMP-dependent protein kinase (PKA), the cellular effector of cyclic AMP-mediated signal transduction. An isoform of the PKA type II R subunit (RII), cARP, is a polyfunctional protein, present in most tissues and cells. It is expressed in salivary and other glands of rodents, and secreted into the saliva of rats and Man. The aim of the present study was to determine the expression of cARP in human salivary glands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…The presence of PKA RII and C subunits in several cytoplasmic regions of striated duct cells presumably reflects binding to other AKAPs and their role in a variety of cellular functions. We previously demonstrated that PKA RII subunits are present in the secretory granules of human salivary gland acinar cells (23) and are secreted into saliva (47). The results of the present study confirm that PKA RII subunits are associated with small secretory granules and vesicles in the apical cytoplasm of human striated duct cells (23), as well as with the apical cell membrane.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The presence of PKA RII and C subunits in several cytoplasmic regions of striated duct cells presumably reflects binding to other AKAPs and their role in a variety of cellular functions. We previously demonstrated that PKA RII subunits are present in the secretory granules of human salivary gland acinar cells (23) and are secreted into saliva (47). The results of the present study confirm that PKA RII subunits are associated with small secretory granules and vesicles in the apical cytoplasm of human striated duct cells (23), as well as with the apical cell membrane.…”
Section: Discussionsupporting
confidence: 89%
“…We previously demonstrated that PKA RII subunits are present in the secretory granules of human salivary gland acinar cells (23) and are secreted into saliva (47). The results of the present study confirm that PKA RII subunits are associated with small secretory granules and vesicles in the apical cytoplasm of human striated duct cells (23), as well as with the apical cell membrane. We now show that PKA C subunits also are associated with these small granules and vesicles.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Amylase and salivary agglutinin [recently demonstrated to be identical to the lung scavenger receptor cysteine-rich protein gp-340 (Prakobphol et al 2000)] are present in the rER, Golgi complex, and in forming and mature granules of parotid and submandibular serous cells (Takano et al 1991(Takano et al ,1993. Acidic proline-rich proteins and the proline-rich polypeptide P-C also are present in the secretory granules of these cells (Takano et al 1993;Kimura et al 1998), and lysozyme and cyclic AMP receptor proteins are present in the serous granules of all three major salivary glands (Machino et al 1986;Miyazaki et al 2001;Piludu et al 2002). In many species, including humans, the secretory granules of serous salivary gland cells display a variety of substructures (reviewed in Tandler and Phillips 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Norepinephrine and vasoactive intestinal peptide stimulate cAMP production in rabbit SMG striated ducts (30), and sympathetic nerve stimulation depletes apical secretory granules in cat SMG striated ducts (31). We have shown that the regulatory and catalytic subunits of type II PKA are associated with the luminal membrane and the small apical secretory vesicles in human striated duct cells (32; Zinn et al, manuscript in preparation). Activation of Gα s and local generation of cAMP could activate PKA, leading to granule exocytosis and/or electrolyte reabsorption, e.g., involving the cystic fibrosis transmembrane conductance regulator (CFTR; 33), by striated duct cells.…”
Section: Discussionmentioning
confidence: 98%